KEBIJAKAN MONETER SEBAGAI PENGENDALI INFLASI DAN NILAI TUKAR - Harsono, Heri Budi; Janwri, Yadi; Hasanuddin, Muhammad (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2025)
The central bank plays a crucial role in the economy through the implementation of monetary policy to maintain inflation and exchange rate stability. As an inflation controller, the central bank uses instruments such as interest rates, open market operations, and mandatory reserve settings to control the money supply and adjust aggregate demand. Tight monetary policy is applied to suppress inflation, while expansionary policies are carried out in weak economic conditions to promote growth. On the other hand, in maintaining exchange rate stability, the central bank can intervene in the foreign exchange market to reduce currency volatility and maintain economic competitiveness. With price and exchange rate stability maintained, the economy can grow sustainably and avoid uncertainty. The role of the central bank becomes increasingly important in the face of complex global and domestic dynamics, and requires good coordination with fiscal policy to achieve optimal macroeconomic objectives. The economic development of a country, including in Indonesia, is certainly inseparable from the monetary and fiscal policies pursued by each country concerned. But the monetary and fiscal policies pursued vary by country depending on the real economic conditions, direction, and development goals to be achieved. Monetary and fiscal policy management in principle aims to maintain the inflation rate by regulating the circulation of money and interest rates that tend to increase in society. Bank Indonesia is an independent institution that has the task of determining and implementing monetary policy so that the value of the rupiah remains stable and the inflation rate can be controlled in order to maintain and increase Indonesia's economic growth. Keywords: monetary, inflation, central bank